Optimalisasi Suhu Karbonisasi Terhadap Rendemen Pada Proses Pembuatan Arang Aktif - Lelawati Lelawati (MAJALAH TEKNIK SIMES, 2015)
Coconut shell is an excellent material to be made of activated carbon, this is because the carbon which has a high absorption capacity , absorption activated charcoal can be described with a number of surface area which ranges from 1000 to 2000 m2 per gram . Along with the development of the industry , the needs of active charcoal also increased. Results can be obtained in the yield of coconut shell carbonization temperature at a temperature of 500 ° C , 600 ° C , 700 ° C , 800 ° C and 900 ° C. The difference in raw materials used and how activation can cause the nature and quality of activated charcoal differently.